Asymmetric nanocapsules via elongated liposome templated polymerization (ELTP) mediated by RAFT polymerization - Yunxin Xiao; Alexander W. Jackson; Angel Tan; John F. Quinn; Simon Crawford; Ben J. Boyd (Drug Delivery and Translational Research, 2025)
Polymeric nanocapsules comprised of hydrophobic shells and hollow aqueous interiors are an extremely useful class of nanomaterial, particularly in the encapsulation and controlled delivery of hydrophilic cargo. Generally prepared via droplet or latex templation approaches, polymeric nanocapsules are mostly spherical. Controlling the morphology of hollow nanocapsules is an intriguing design challenge. Non-spherical, or elongated, templates are often inorganic materials which do not directly impart a hollow interior, and their post-polymerization removal is not straightforward. This study outlines a novel strategy for the preparation of elongated nanocapsules, wherein elongated liposomes are deployed as hollow templates. Initially, ciprofloxacin drug nanocrystals were utilized to facilitate the formation of elongated liposomes, followed by adsorption of reversible addition-fragmentation chain transfer (RAFT) oligomers. Subsequent chain-extension polymerization furnished the desired elongated nanocapsule morphology. This proof-of-concept study contributes towards the goal of elongated nanocapsule synthesis, a morphology which can impart improved circulation times in the field of drug delivery. Graphical Abstract

Regulation of CO2 by the sea in areas around Latin America in a context of climate change - V. Lutz; M. Chidiak; R. Frouin; R. Negri; A. I. Dogliotti; E. Santamaria-del-Angel; C. F. Berghoff; J. Rojas; C. Filipello; Y. Astor; V. Segura; A. Gonzalez-Silvera; et al. (Environmental Monitoring and Assessment, 2023)

Molecular evidence for a clonal relationship between synchronous uterine endometrioid carcinoma and ovarian clear cell carcinoma: a new example of “precursor escape”? - Cindy Hsuan Weng; Ren-Chin Wu; Shu-Jen Chen; Hua-Chien Chen; Kien Thiam Tan; Yun-Shien Lee; Shih-Sin Huang; Lan-Yan Yang; Chin-Jung Wang; Hung-Hsueh Chou; An-Shine Chao; Angel Chao; et al. (Journal of Molecular Medicine, 2021)

Coupling in vitro cell culture with synchrotron SAXS to understand the bio-interaction of lipid-based liquid crystalline nanoparticles with vascular endothelial cells - Yuen Yi Lam; Adrian Hawley; Angel Tan; Ben J. Boyd (Drug Delivery and Translational Research, 2020)

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

A simple and inexpensive enteric-coated capsule for delivery of acid-labile macromolecules to the small intestine - Darren S. Miller; Anne Michelle Parsons; John Bresland; Paul Herde; Duc Minh Pham; Angel Tan; Hung-yao Hsu; Clive A. Prestidge; Tim Kuchel; Rezaul Begg; Syed Mahfuzul Aziz; Ross N. Butler (Journal of Zhejiang University-SCIENCE B, 2015)

First in man bioavailability and tolerability studies of a silica–lipid hybrid (Lipoceramic) formulation: a Phase I study with ibuprofen - Angel Tan; Nasrin Ghouchi Eskandar; Shasha Rao; Clive A. Prestidge (Drug Delivery and Translational Research, 2014)

Transforming Lipid-Based Oral Drug Delivery Systems into Solid Dosage Forms: An Overview of Solid Carriers, Physicochemical Properties, and Biopharmaceutical Performance - Angel Tan; Shasha Rao; Clive A. Prestidge (Pharmaceutical Research, 2013)

Silica-Lipid Hybrid (SLH) Versus Non-lipid Formulations for Optimising the Dose-Dependent Oral Absorption of Celecoxib - Angel Tan; Andrew K. Davey; Clive A. Prestidge (Pharmaceutical Research, 2011)